Quantitative Analysis of the Reaction Stock Price in Transportation and Tourist Companies Listed on Indonesia Stock Exchange Towards Elimination of Implementing on Community Activities Restrictions (PPKM) - Meilan, Ria; Muttaqien, Fauzan; Nuha, Sukma Uli (OECONOMICUS Journal of Economics, 2023)
This study aims to analyze whether there were differences in Abnormal Return and Trading Volume Activity in the stock prices of the Indonesia Stock Exchange in the transportation and tourism sectors before and after the PPKM abolition policy. The sample in this study was by means of purposive sampling with a total of 22 companies from 22 total population of companies in the transportation and tourism sector which are listed on the Indonesia Stock Exchange. Regression analysis was carried out in this study with an event study approach. Hypothesis testing was carried out using the Paired Sample T-Test and the Wilcoxon Signed Rank Test. The results of the research test show that there is no significant difference in the abnormal return and trading volume activity of stock prices on the repeal of the PPKM policy in Indonesia. The implications of this study are expected to add references for future researchers in examining abnormal returns and trading volume activity in stock prices associated with events that were happening at that time. The novelty of this research lies in the events that became the basis of the research, namely before and after the policy of eliminating PPKM after the Covid 19 pandemic hit Indonesia.